Developing Navy Capability to Recover Forces in Chemical, Biological, and Radiological Hazard Environments - Resnick, Adam C. (RAND Corporation, 2013)
Recovering amphibious forces can be complicated if ashore forces come under attack from enemy weapons, particularly chemical, biological, or radiological weapons. This report assesses current policies and capabilities pertaining to the recovery and decontamination of ashore forces and identifies policy options the Navy could pursue to better perform this mission.